Rapid Screen for Antiviral T‐Cell Immunity with Nanowire Electrochemical Biosensors (Adv. Mater. 29/2022). Issue 29 (21st July 2022) - Nami, Mohsen; Han, Patrick; Hanlon, Douglas; Tatsuno, Kazuki; Wei, Brian; Sobolev, Olga; Pitruzzello, Mary; Vassall, Aaron; Yosinski, Shari; Edelson, Richard; Reed, Mark
Abstract : Human T‐Cell Analysis Researchers at Yale University have designed a new blood test for rapid electronic detection of T‐cell immunity in humans using silicon nanowire arrays. In article number 2109661, Mohsen Nami, Richard Edelson, and co‐workers demonstrate a novel device in near‐instantaneous assessment of individual immunity against COVID‐19, and describe potential applications as a Point‐of‐Care tool for screening vaccine responses or monitoring patient immunity in cancer, autoimmunity, and infectious diseases.